SOSIALISASI PENGARUH KEBUGARAN FISIK TERHADAP PRODUKTIVITAS REMAJA DAN KESEHATAN LANSIA DI DESA - Yona Bayu Prasetyo; Lukas Susanto; Ghon Lisdiantoro; Agung Dwi darmawan (Jurnal Berdaya Mandiri, 2025)
Physical fitness is an important factor in supporting individual productivity across all age groups. Adolescents with good physical fitness tend to be more productive, focused, and active in both academic and social activities. On the other hand, physically active elderly individuals generally enjoy a higher quality of life and have a lower risk of degenerative diseases. This community service program aims to provide education and outreach to the public on the importance of physical fitness in enhancing adolescent productivity and maintaining the health of the elderly. The activity was conducted in Simbatan Nguntoronadi, Magetan, involving participants from both adolescent and elderly groups. The methods used included educational sessions, demonstrations of simple physical exercises, and interactive Q&A sessions. The results of the activity showed an increase in community understanding of the importance of physical activity, as well as a commitment to integrating physical fitness into daily routines. This initiative is expected to serve as an initial step toward building awareness and promoting a sustainable active lifestyle. Keywords: Physical Fitness, Adolescents, Elderly, Productivity, Health